Tecnica, potere e sicurezza digitale nelle Smart Cities: alcuni spunti - Garasic, Mirko Daniel (Mechane, 2025)
The concept of algorpolitics, previously developed in other writings, finds crucial application in the context of smart cities, where technology, particularly that based on algorithms and artificial intelligence (AI), plays an increasingly central role in the management of urban infrastructures, public services and citizens’ daily lives. This concept would like to highlight the complexities and ethical risks arising from the increasing automation of city governance and algorithmic control, analysing the link between technology and power. In this paper, I will look into some of the ethical challenges that are ever more present in a specific setting such as that of a smart city.